2013
DOI: 10.1007/s00586-013-2817-2
|View full text |Cite
|
Sign up to set email alerts
|

Anterior approach versus posterior approach for the treatment of multilevel cervical spondylotic myelopathy: a systemic review and meta-analysis

Abstract: Purpose To compare the clinical outcomes, complications, and surgical trauma between anterior and posterior approaches for the treatment of multilevel cervical spondylotic myelopathy. Study design Systematic review and meta-analysis. Methods We searched MEDLINE, EMBASE, and the Cochrane Central Register of Controlled Trials databases for randomized controlled trials or non-randomized controlled trials that compared anterior and posterior surgical approaches for the treatment of multilevel cervical spondylotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
107
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(117 citation statements)
references
References 31 publications
5
107
0
5
Order By: Relevance
“…The systemic review and meta-analysis of the results of cervical decompression for spondylotic myelopathy when done anteriorly or posteriorly by Zhu et al [54] although based on just eight studies, none of them prospective or randomised, came out with a clear message, multi-level decompression should be done from behind. Five hundred and thirty patients were studied, 245 patients had anterior surgery, and 285 posterior surgery.…”
Section: Cervical Spinementioning
confidence: 99%
“…The systemic review and meta-analysis of the results of cervical decompression for spondylotic myelopathy when done anteriorly or posteriorly by Zhu et al [54] although based on just eight studies, none of them prospective or randomised, came out with a clear message, multi-level decompression should be done from behind. Five hundred and thirty patients were studied, 245 patients had anterior surgery, and 285 posterior surgery.…”
Section: Cervical Spinementioning
confidence: 99%
“…However, both approaches resulted in the same neural function recovery rate at 5 years follow-up [10,11]. This is because anterior surgeries allow direct removal of anterior pathologies that cause compression to the spinal cord.…”
Section: Anterior Surgical Approachmentioning
confidence: 93%
“…Nevertheless, it was found that in more than 5 years post operation, the complication rate was similar between anterior and posterior surgeries [10]. The most common complication found following anterior surgeries is pseudoarthrosis [11]. The authors [11] suggested that this is due to the technical reasons and bone graft quality.…”
Section: Anterior Surgical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…
Dear Editor,We read with great interest the recent paper by Zhu et al [1] ''Anterior approach versus posterior approach for the treatment of multilevel cervical spondylotic myelopathy: a systemic review and meta-analysis'' published online in European Spine Journal. In this article, the authors performed a meta-analysis to compare the clinical outcomes, complications, and surgical trauma between anterior and posterior approaches for the treatment of multilevel cervical spondylotic myelopathy (CSM), and did very well.
…”
mentioning
confidence: 99%